(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The advancement of artificial intelligence (AI) has consolidated the “AI First” paradigm, which promises significant efficiency gains. In Brazilian constitutionalism, however, the prevalence of the principle of human dignity requires that technology remain a means, not an end. The central research question addressed in this article is: to what extent is the prioritization of technical efficiency compatible with the realization of citizenship and the protection of dignity? To answer this question, the study adopts a theoretical-exploratory, qualitative, and deductive methodology, drawing on the reflections of Jacques Ellul and Byung-Chul Han. This approach highlights risks such as bias, opacity, depersonalization, surveillance, and algorithmic management of labor, while at the same time proposing a model of technological governance that adheres to the imperatives of human centrality. The article concludes that AI can only serve as an instrument of citizenship when it strengthens — rather than replaces — human experience, subordinating efficiency to transparency, equity, social participation, and data protection, with dignity and citizenship as the central decision-making criteria.